Context Clues and Reading Comprehension - C, Emejidio (International Journal of Psychosocial Rehabilitation, 2020)
There is a lingering progress in reading comprehension skill compared to other subject skills. Unfamiliar word is one of the factors that affects one’s reading comprehension. A reader cannot comprehend effectively if he/she does not know the meaning of a certain word. The objective of the study was to find out the use of context clues towards reading comprehension of Jose Abad Santos High School. Particularly, the researchers’ goal was to know how context clues aid in improving the reading comprehension difficulties of the students. The 15 participants were chosen according to convenient sampling technique and from the section 22 of Jose Abad Santos High School at Binondo, Manila. The students were given a pre-test that served as a diagnostic test of the seven-day treatment which involves exploring the participants’ use of context clues in reading comprehension for seven days. The post-test was given to the students after the treatment used was effective. The pre-test obtained a mean of 10.93 and the computed standard deviation is 3.432. Then, the post- test obtained a mean of 20.60 and the computed standard deviation is 4.405. The researchers concluded that the students need improvement due to their low initial performance. After conducting the treatment, the post-test mean is higher than the pre-test mean. Hence, it can be concluded that the observed differences between the two means are significantly different. With this, the researchers recommend